2007
DOI: 10.1074/jbc.r600036200
|View full text |Cite
|
Sign up to set email alerts
|

Arylalkylamine N-Acetyltransferase: “the Timezyme”

Abstract: Arylalkylamine N-acetyltransferase controls daily changes in melatonin production by the pineal gland and thereby plays a unique role in biological timing in vertebrates. Arylalkylamine N-acetyltransferase is also expressed in the retina, where it may play other roles in addition to signaling, including neurotransmission and detoxification. Large changes in activity reflect cyclic 3,5-adenosine monophosphate-dependent phosphorylation of arylalkylamine N-acetyltransferase, leading to formation of a regulatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
347
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 374 publications
(374 citation statements)
references
References 84 publications
17
347
0
3
Order By: Relevance
“…This goldfish AANAT-2 deduced amino acid sequence shows more that 90% identity with Aanat-2 sequences from other fish species such as zebrafish, seabream, rainbow trout or pike. Moreover, characteristic binding motifs, phosphorylation sites and conserved regions of the AANAT family (Ganguly et al 2002;Klein, 2007) are identified in the goldfish sequence, supporting the homology of the encoded protein.…”
Section: Cloning Of Goldfish Aanat-2 and Hiomt-2 Genesmentioning
confidence: 86%
See 3 more Smart Citations
“…This goldfish AANAT-2 deduced amino acid sequence shows more that 90% identity with Aanat-2 sequences from other fish species such as zebrafish, seabream, rainbow trout or pike. Moreover, characteristic binding motifs, phosphorylation sites and conserved regions of the AANAT family (Ganguly et al 2002;Klein, 2007) are identified in the goldfish sequence, supporting the homology of the encoded protein.…”
Section: Cloning Of Goldfish Aanat-2 and Hiomt-2 Genesmentioning
confidence: 86%
“…Moreover, as occurs in zebrafish (Gothilf et al, 1999), a positive signal for AANAT-2 transcript is also found in goldfish retina, in spite of the general acceptance that Aanat-2 is more specifically expressed in the pineal organ of teleost (Klein, 2007, Falcon, 2009. One interesting evidences from present results is the peripheral expression of both enzymes, AANAT-2 and HIOMT-2, which supports MEL synthesis in such peripheral locations.…”
Section: Distribution Of Aanat-2 and Hiomt-2 Mrna In Goldfishmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally accepted that the diurnal profile of the blood melatonin concentration results from daily variations in the activity of pineal arylalkylamine-N-acetyltransferase (AANAT; E.C.2.3.1.87), a key enzyme in melatonin biosynthesis (Klein, 2007). The daily profile of AANAT activity in chickens was found to be affected by the season, regardless of artificial LD 12:12 conditions imposed from the day of hatch Piesiewicz et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%